Education on the Administration of Katuk Leaves to Increase Breast Milk Production in Postpartum Mothers at Pasar X Community Health Center, Bandar Khalipah Village, Percut Sei Tuan District, 2025 - Sri Putriani Sinaga; Desikawali Pardede; Meria Turnip (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
Breast milk production during the postpartum period is a physiological phenomenon determined by the synergy of hormonal regulation, maternal psychological stability, and adequate nutritional intake. This community service activity (PkM) aimed to increase the use of katuk leaves as an effort to stimulate breast milk volume. The participants consisted of 12 postpartum mothers selected based on predetermined inclusion criteria. Breast milk production was measured based on observational results and mothers’ subjective reports.The implementation method used a pretest–posttest design. The results showed that before the intervention, 7 respondents (58.3%) experienced a decrease in breast milk production, and no respondents showed an increase. After being given katuk leaf intervention for a certain period, 5 participants (41.7%) experienced an increase in breast milk production, 4 participants (33.3%) experienced no change, and 3 participants (25.0%) experienced a decrease. The mean breast milk production score before the intervention was 2.58 (SD = 0.515) and decreased to 1.83 (SD = 0.835) after the intervention. These findings reinforce the role of katuk leaves as an effective lactagogue agent in stimulating increased breast milk volume in postpartum mothers and suggest that it can be used as a non-pharmacological alternative to support successful lactation.